2015
DOI: 10.3174/ajnr.a4425
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic 4D MRI for Characterization of Parathyroid Adenomas: Multiparametric Analysis

Abstract: BACKGROUND AND PURPOSE:The hypervascular nature of parathyroid adenomas can be explored by proper dynamic imaging to narrow the target lesions for surgical exploration. The purpose of this study was to establish MR perfusion characteristics of parathyroid adenomas to differentiate them from their mimics, such as subjacent thyroid tissue and cervical lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 25 publications
(22 reference statements)
0
31
0
5
Order By: Relevance
“…Because of the lack of adipose tissue in parathyroid adenomas, high signal intensity on T2-weighted images is seen typically at MR imaging, which enables detection of adenomas (27). Because of advances in technology, its accuracy has increased even further with the use of dynamic contrast materialenhanced imaging (16). In our study, however, use of MR imaging alone was substantially less successful than use of the combination of PET and MR imaging.…”
Section: Discussionmentioning
confidence: 65%
“…Because of the lack of adipose tissue in parathyroid adenomas, high signal intensity on T2-weighted images is seen typically at MR imaging, which enables detection of adenomas (27). Because of advances in technology, its accuracy has increased even further with the use of dynamic contrast materialenhanced imaging (16). In our study, however, use of MR imaging alone was substantially less successful than use of the combination of PET and MR imaging.…”
Section: Discussionmentioning
confidence: 65%
“…[41][42][43] Dynamic contrast-enhanced MRI may also be used to localize parathyroid adenomas, taking advantage of the hypervascular nature and differential contrast washout from parathyroid adenomas compared with lymph nodes and thyroid tissue. [44][45][46]…”
Section: Ct and Mrimentioning
confidence: 99%
“…This exploits similar principles to 4D-CT and the enhancement and wash out characteristics of parathyroid adenomata (though lipidrich adenomata have been described to demonstrate more delayed wash out relative to the more cellular lesions). A retrospective study by Nael et al [8] has reported a high (96%) diagnostic accuracy in adenoma The images demonstrate an extra-thyroid, right-sided septated cystic-solid lesion within level VI of the neck and the arrow points to non-dependent, subtle intralesional soft tissue. There is effacement of the right pyriform fossa more superiorly.…”
Section: Cross-sectional Imagingmentioning
confidence: 99%